The Horizontal Alignment Redesign of Connecting Roads in the Coal Area: A Case of the Section Sulit Air – Rawang STA 6+300 – 6+600 West Sumatera - M Roni Gustian; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2023)
The construction of the Sulit Air Road - Rawang, Sawahlunto City, is expected to be a solution to shorten travel time and ensure the comfort and safety of road users. The data used in this paper uses secondary data. Using the Bina Marga method, this journal aims to redesign the Sulit Air Road – Rawang, Sawahlunto City at STA 6+300 – STA 6+600. The study results show that the Sulit Air – Rawang is a class collector primer Road with flat terrain with a width of 4.5 m, design parameters design speed (VR) of 60 km/hour, and a maximum slope (e) of 8%. From the calculations, the design radius (R) is 350 m. The curved horizontal length (Lc) is 87.120 m. In this journal, the authors take the FC (Full Circle) type of curved horizontal line that is safe for the rider according to the conditions in the field.